Angiopoietin-2 blocking antibodies reduce early atherosclerotic plaque development in mice. Issue 2 (August 2015) - Theelen, Thomas L.; Lappalainen, Jari P.; Sluimer, Judith C.; Gurzeler, Erika; Cleutjens, Jack P.; Gijbels, Marion J.; Biessen, Erik A.L.; Daemen, Mat J.A.P.; Alitalo, Kari; Ylä-Herttuala, Seppo
Abstract: Objective: Angiopoietin-2 (Ang-2) blocking agents are currently undergoing clinical trials for use in cancer treatment. Ang-2 has also been associated with rupture-prone atherosclerotic plaques in humans, suggesting a role for Ang-2 in plaque stability. Despite the availability of Ang-2 blocking agents, their clinical use is still lacking. Our aim was to establish if Ang-2 has a role in atheroma development and in the transition of subclinical to clinically relevant atherosclerosis. We investigated the effect of antibody-mediated Ang-2 blockage on atherogenesis after in a mouse model of atherosclerosis. Methods: Hypercholesterolemic (low-density lipoprotein receptor −/− apolipoprotein B 100/100 ) mice were subjected to high-cholesterol diet for eight weeks, one group with and one group without Ang-2 blocking antibody treatment during weeks 4–8.To enhance plaque development, a peri-adventitial collar was placed around the carotid arteries at the start of antibody treatment. Aortic root, carotid arteries and brachiocephalic arteries were analyzed to evaluate the effect of Ang-2 blockage on atherosclerotic plaque size and stable plaque characteristics. Results: Anti-Ang-2 treatment reduced the size of fatty streaks in the brachiocephalic artery (−72%, p < 0.05). In addition, antibody-mediated Ang-2 blockage reduced plasma triglycerides (−27%, p < 0.05). In contrast, Ang-2 blockage did not have any effect on the size or composition (collagen content, macrophage percentage, adventitial microvessel density) of pre-existing plaques in the aortic root or collar-induced plaques in the carotid artery. Conclusions: Ang-2 blockage was beneficial as it decreased fatty streak formation and plasma triglyceride levels, but had no adverse effect on pre-existing atherosclerosis in hypercholesterolemic mice. Highlights: Antibody-mediated Ang-2 blockage delays fatty streak formation in mice. Ang-2 blockage lowers plasma triglyceride levels. Ang-2 blockage has no negative effects on preexisting atherosclerosis.